A Phosphane‐Free, Atom‐Efficient Cross‐Coupling Reaction of Triarylbismuths with Acyl Chlorides Catalyzed by MCM‐41‐Immobilized Palladium Complex. Issue 7 (25th January 2013) - Zhao, Hong; Yin, Lin; Cai, Mingzhong
Abstract: The first phosphane‐free, heterogeneous, atom‐efficient cross‐coupling reaction of triarylbismuths and acyl chlorides was achieved in N ‐methylpyrrolidone (NMP) with Bu3 N as the base at 80 °C in the presence of 1.5 mol‐% MCM‐41‐immobilized bidentate nitrogen palladium complex [MCM‐41–2N‐Pd(OAc)2, MCM = mobile crystalline material] to yield a variety of unsymmetrical biaryl ketones in good to excellent yields. This heterogeneous palladium catalyst exhibited a high activity, which was similar to that of Pd(PPh3 )4 . The catalyst can be recovered by a simple filtration of the reaction solution and recycled in at least 10 consecutive trials without any decrease in activity. Our system not only avoids the use of phosphane ligands, but also solves the basic problem of palladium catalyst recovery and reuse. Abstract : The first phosphane‐free, heterogeneous, atom‐efficient cross‐coupling reaction of triarylbismuth compounds and acyl chlorides was achieved in N ‐methylpyrrolidone with Bu3 N as the base at 80 °C in the presence of 1.5 mol‐% MCM‐41‐immobilized bidentate nitrogen palladium complex [MCM‐41–2N‐Pd(OAc)2 ] to yield a variety of unsymmetrical biaryl ketones in good to excellent yields.